Simulation and multi-objective optimization of a combined heat and power (CHP) system integrated with low-energy buildings. (March 2016) - Pirkandi, Jamasb; Jokar, Mohammad Ali; Sameti, Mohammad; Kasaeian, Alibakhsh; Kasaeian, Fazel
Abstract: One of the novel applications of gas turbine technology is the integration of combined heat and power (CHP) system with micro-gas turbine which is spreading widely in the field of distributed generation and low-energy buildings. It has a promising great potential to meet the electrical and heating demands of residential buildings. In this study, a MATLAB code was developed to simulate and optimize the thermoeconomic performance of a gas turbine based CHP cycle. Three design parameters of this cycle considered in this research are compressor pressure ratio, turbine inlet temperature, and air mass flow rate. Firstly, two objective functions including exergetic efficiency and net power output were chosen to achieve their maximum level. Variation of exergy destruction rate and exergetic efficiency with three turbine inlet temperatures (1000, 1100, and 1200 K) and three air mass flow rates (0.25, 0.3, and 0.35 kg/s) were also studied for each component. Exergetic efficiency increased relatively to maximum 3% within this temperature limit. Based on the exergetic analysis, suggestions were given for reducing the overall irreversibility of the thermodynamic cycle. To have a good insight into this study, a sensitivity analysis for important parameters was also carried out. Finally, based on the exergy analysis and utilization of economic and environmental functions, a multi-objective approach was taken to optimize the system performance. Graphical abstract: Highlights: Proposed a methodology for design of MGT-based CHP systems to be used by decision makers. A computer simulation for the performance of the building integrated CHP system. A Pareto multiobjective genetic optimization approach for system performance. Offered suggestions to reduce the overall system irreversibilities. Optimum levels for thermoenviroeconomic objective and exergetic efficiency.